(3JHjf GdMbGFb deG ajg ef JHjf eG GcJfR ef GdObGFbs - (3GdRjdYj, YKeGf Hf Ydj Hf eMLf, J (B743 (3g`s ((3eMeO MLGRj GdbJdjs)
(3ChdgG (B:s
(3HYO GdehJ hGdhUjI hgj Jedjc GdeGd HYO GdehJ dG jchfGf EdG eVGajf EPG GdGjUG aj GdMGd dG jJUhQ EdG EPG LYd eLGRG Yf GdhcGdIs
(3BNQgG (B:s
(3CUdgG SJI hJYhd Edi KeGfjI aEPG GSJhaJ GdCNJ fUjHgG hgh KdGKI Hbj NeSI hdh LYdJ cCfgG de Jcf dcGfJ ef SJI hJYhd Hge Edi SHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 210s
(3eYLe GdeDdajf (B2 / 365s
(3cTa GdXfhf (B2/ 1515s
(3gOjI GdYGQajf (B1 / 655s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs